# Triangle abc is a right triangle. point d is the midpoint of side ab and point e is the midpoint of side ac. the measure of angle ade is 47°. triangle abc with segment de. angle ade measures 47 degrees. the following flowchart with missing statements and reasons proves that the measure of angle ecb is 43°: statement, measure of angle ade is 47 degrees, reason, given, and statement, measure of angle dae is 90 degrees, reason, definition of right angle, leading to statement 3 and reason 2, which further leads to statement, measure of angle ecb is 43 degrees, reason, substitution property. statement, segment de joins the midpoints of segment ab and ac, reason, given, leading to statement, segment de is parallel to segment bc, reason, midsegment theorem, which leads to angle ecb is congruent to angle aed, reason 1, which further leads to statement, measure of angle ecb is 43 degrees, reason, substitution property. which statement and reason can be used to fill in the numbered blank spaces? corresponding angles are congruent triangle sum theorem measure of angle aed is 43°. alternate interior angles are congruent base angle theorem measure of angle aed is 47° base angle theorem corresponding angle are congruent measure of angle aed is 43°. alternate interior angles are congruent triangle sum theorem measure of angle aed is 47° The correct answer was given: Brain
The answer would be A. 1 1/5

48/40 = 1 8/40

1 8/40 Simplify to 1 1/5

Hope this helps! The correct answer was given: Brain
I believe it is 60-10=x because it says she purchased it with 60\$ but recieved 10\$ in change causing the amount we dont know to be a variable such as “x” The correct answer was given: Brain

its 60-10+x why, because she bought the dress with \$60 and she received \$10 dollars back. We don’t know the variable.

Step-by-step explanation: The correct answer was given: Brain

k = 13The smallest zero or root is x = -10

===============================

Work Shown:

note: you can write “x^2” to mean “x squared”

f(x) = x^2+3x-10

f(x+5) = (x+5)^2+3(x+5)-10 … replace every x with x+5

f(x+5) = (x^2+10x+25)+3(x+5)-10

f(x+5) = x^2+10x+25+3x+15-10

f(x+5) = x^2+13x+30

Compare this with x^2+kx+30 and we see that k = 13

Factor and solve the equation below

x^2+13x+30 = 0

(x+10)(x+3) = 0

x+10 = 0 or x+3 = 0

x = -10 or x = -3

The smallest zero is x = -10 as its the left-most value on a number line.